Choosing Wisely Brazil initiative for Women’s Health/Pelvic Floor Physical Therapy: study protocol - Driusso, Patricia; Reis, Felipe José Jandre dos; Rodrigues, Jessica Cordeiro; Pasqualotto, Luisa; Catai, Camila Chiazuto; Mascarenhas, Lilian Rose; Botelho, Simone; Jorge, Cristine Homsi (Universidade Federal de São Carlos, 2022)
INTRODUCTION: The Choosing Wisely initiative aims to promote discussions among health professionals and patients to reduce low-value care that confers no benefit or can cause harm to health. OBJECTIVE: To describe the process for developing the Brazilian Choosing Wisely list for Women’s Health/Pelvic Floor Physical Therapy. METHODS: The research will be conducted in three stages. In the first stage, physical therapists with experience in women’s health/pelvic floor will be invited to compose a panel of experts and respond to a form. The Delphi method will be used to derive a list of evidence-based statements. In the second stage, members of the research team will review all the recommendations provided by the expert panel. In the third stage, a sample of physical therapists will vote on the previously selected statements. The recommendations with the most votes in the national survey will be submitted to Choosing Wisely Brazil, and a final list of recommendations will be published.
Keywords: Evidence-Based Practice; Clinical Decision Making; Health education; Recommendations; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::GINECOLOGIA E OBSTETRICIA